2023
DOI: 10.1021/acschemneuro.3c00074
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Computational Insights, and Evaluation of Novel Sigma Receptors Ligands

Abstract: The development of diazabicyclo[4.3.0]nonane and 2,7-diazaspiro[3.5]nonane derivatives as sigma receptors (SRs) ligands is reported. The compounds were evaluated in S1R and S2R binding assays, and modeling studies were carried out to analyze the binding mode. The most notable compounds, 4b (AD186, K iS1R = 2.7 nM, K iS2R = 27 nM), 5b (AB21, K iS1R = 13 nM, K iS2R = 102 nM), and 8f (AB10, K iS1R = 10 nM, K iS2R = 165 nM), have been screened for analgesic effects in vivo, and their functional profile was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Phenytoin is an allosteric modulator for the S1R, and it differentially modulates the affinity of S1R ligands on the basis of their agonist or antagonist profile. 22,23 Indeed, phenytoin potentiates the receptor binding affinity of S1R agonists and produces no effects or slightly reduced receptor binding affinity for S1R antagonists. The functionality of compound 1 on S1R was determined by radioligand binding assay using rat liver in the presence of phenytoin, together with the known S1R agonist SKF-10 047 and antagonist BD-1063 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenytoin is an allosteric modulator for the S1R, and it differentially modulates the affinity of S1R ligands on the basis of their agonist or antagonist profile. 22,23 Indeed, phenytoin potentiates the receptor binding affinity of S1R agonists and produces no effects or slightly reduced receptor binding affinity for S1R antagonists. The functionality of compound 1 on S1R was determined by radioligand binding assay using rat liver in the presence of phenytoin, together with the known S1R agonist SKF-10 047 and antagonist BD-1063 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1R and S2R radioligand binding assays involve the use of liver homogenates from male Sprague Dawley rats as previously reported. 21,22 In vitro S1R ligand binding assays were performed in Tris buffer (50 mM, pH 8), with [ 3 H](+)-pentazocine (2 nM) as radioligand. The final volume was 0.5 mL.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro S2R ligand binding assays were performed, using [ 3 H]-DTG (2 nM; K d = 17.9 nM) as a radioligand, (+)-pentazocine (5 μM) as S1R masking agent, and DTG (10 μM) for the measurement of non-specific binding. The final volume was 0.5 mL [ 54 ]. A millipore filter apparatus was employed to separate bound and free radioligands via filtration under conditions of reduced pressure through Whatman GF 6 glass fiber filters.…”
Section: Methodsmentioning
confidence: 99%
“…in capsaicin and formalin models [ 2 , 3 ]. In order to unambiguously determine the functional profile of σ 1 R ligands, in vitro studies were also performed, including a well-established phenytoin-based functional assay [ 9 ]. Previous studies have shown that phenytoin, a low-potent allosteric modulator for the σ 1 R, differentially modulates the affinity of σ 1 R ligands depending on their agonist versus antagonist functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that phenytoin, a low-potent allosteric modulator for the σ 1 R, differentially modulates the affinity of σ 1 R ligands depending on their agonist versus antagonist functionality. Phenytoin potentiates the receptor binding affinity of σ 1 R agonists, however, it produces no effects or slightly reduced receptor binding affinity for σ 1 R antagonists [ 9 ]. In fact, the results of phenytoin-based functional assay correlate with the in vivo activity of tested compounds, but the weak point is that the differences in binding affinities with the phenytoin are very small compared to the values obtained for compounds without an allosteric modulator [ 9 ].…”
Section: Introductionmentioning
confidence: 99%